ANALISIS STRUKTUR DAN KINERJA: STUDI PADA INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Suhel Suhel (Jurnal Ekonomi Pembangunan, 2015)
The existence of Islamic banking in Indonesia is driven by the desire of the people of Indonesia, especially the Muslims who believe that interest is haram. However, the actual principle of sharing in financial institutions has been widely recognized both in the Islamic and non-Islamic countries. During its development, the Islamic banking industry continue to fluctuate in line with the economic situation that occurred. Such as the global financial crisis of 2008, which adversely affected the economy of Indonesia. However, Islamic banking has the durability and good performance. This research analyzes the market structure and performance of the Islamic banking industry in Indonesia. From the research found that the structure of the Islamic banking market in Indonesia led to an oligopoly market structure type 1. In addition a variable structure, market share, FDR and positive influence on the performance of assets, while the NPF negatively affect the performance of the Islamic banking industry in Indonesia. This study suggests necessary regulatory implementation of Islamic banking and Islamic principles consistent run, that will create healthy competition in Islamic banking industry in Indonesia. In addition, Islamic banking needs to continue to improve efficiency in its operations, so that the performance of the industry will remain intact. Keywords: structure, performance, Islamic banking industry.